Plant and natural product based homemade remedies for veterinary uses by the Peul community in Benin - OUACHINOU, Jéronime Marie-Ange Sènami; Adomou, Aristide C.; DASSOU, Gbèwonmèdéa Hospice (My University, 2020)
Ethnopharmacological relevance: Across Africa, Peul community typically rely on plant-based veterinary knowledge to manage common livestock health problems. Unfortunately, their nomadic life-style being affected by conflicts, land tenure constraints, and drought, they have been shifting to a sedentary life. The process of their settlement led to the erosion of the vast ethnoveterinary skills they had acquired over centuries and forced them to replace the plant and other species they used by commercial products. Aim of the study: 1) To collect comprehensive data from the Benin Peul community on common plant-based remedies used to treat livestock diseases and document their preparation and administration. 2) To evaluate the differences and consensus among the Peul community across ecological regions in Benin. Materials and methods: We conducted semi-structured interviews among 88 Peul camps, three (03) bioclimatic zones, and 225 transhumant dialog partners, including agro-pastoralists, healers and pastoralists from mid-July to end of December 2015. Detailed information about homemade herbal remedies (plant species, plant part, manufacturing process) and the corresponding use reports (target animal species, category of use and route of administration) was collected. Results: A total of 418 homemade remedies were reported, of which 235 involved only one plant species (Homemade Single Species Herbal Remedy Reports; HSHR). Information on a total of 310 use reports (UR) were mentioned for the 235 HSHR, and they included 116 plant species belonging to 39 botanical families. Among them, 229 UR were indicated for cattle, 43 UR for poultry, and 38 UR for sheep and goats. The most cited plant species were Khaya senegalensis (19 HSHR; 8.08%), Parkia biglobosa (14 HSHR; 5.95%), Euphorbia unispina (11HSHR; 4.68%), and Anogeissus leiocarpus (6 HSHR; 2.55%). The URs were indicated for the treatment of viral, parasitic and bacterial diseases but also for multifactorial disorders like diarrhoea, fever, threatened abortion, agalactia etc. The number of plants referred to HSHR decreased from Sudanian to Guineo-congolian zones in concordance with the presence of Peuls. Conclusion: The Peul community holds a huge ethnoveterinary knowledge, which needs to be documented, valorised, and promoted. It appears vital to assess phytochemical and pharmacological properties of the most reported species, and their availability across the ecological zones in order to ensure their sustainable use and before this indigenous knowledge disappears completely.
Keywords: Settling process; Peul ethnoveterinary medicine; livestock; ecological zones; Benin